Speed, agility, and lower body power comparisons between collegiate and professional soccer players - Eisenman, M.; Ryan, G.; Phillips, S.; DeJohn, D. (The Journal of Strength and Conditioning Research, 2021)
Soccer requires a combination of speed, agility, and lower body power to successfully compete. While the demands of the sport are similar regardless of level of competition, average player performance on various tests may greatly differ across levels of competition. Coaches and training staffs could benefit from noting these differences in an effort to better identify players and help prepare them for the next level of competition. Purpose: To compare performance on speed, agility, and vertical jump tests between collegiate and professional male soccer players. Methods: 16 Division I NCAA collegiate (C) (Age: 19.8 ± 1.3 years, Height: 1.78 ± 0.07 m, Weight: 72.6 ± 5.7 kg) and 20 third-division USL professional (P) male soccer players (Age: 22.5 ± 1.4 years, Height: 1.80 ± 0.08 m, Weight: 79.1 ± 7.0 kg) completed a test battery designed to measure maximum speed, agility, and lower body power. The test battery included: Pro Agility Shuttle (PAS), L-Drill (L-D), akimbo countermovement jump (CMJ), and 30 m maximum effort sprint (Smax). All athletes were allowed to complete each trial twice, and the best effort was included for analyses. Performance on the PAS and L-D were measured via stopwatches, CMJ on a switch mat, and Smax using GPS bioharnesses. Following completion of all testing, data was inputted and analyzed using independent sample t-tests, with a = 0.05 to denote significant differences between athletes. Results: P performed better in the PAS (P: 4.19 ± 0.21 s, C: 4.69 ± 0.14 s; p < 0.01, ES = 2.80), L-D (P: 7.39 ± 0.28 s, C: 7.74 ± 0.38 s; p < 0.01, ES = 1.05), and had higher Smax (P: 8.8 ± 0.6m/s, C: 8.0 ± 0.4m/s; p < 0.01, ES = 1.57) compared to C. No difference was noted for CMJ between groups (P: 60.7 ± 6.4 cm, C: 57.2 ± 4.9 cm; p = 0.06). Conclusions: Despite the small average age gap (~12%), professional soccer players vastly outperformed the collegiate players on all tests except CMJ. All statistically significant differences also had large effect sizes, indicating a practical difference in tested variables. P outperformed C players by 12% on the PAS, 5% on the L-D, and 10% on Smax. There appears to be a sizable skill gap between NCAA Division I and third-division USL athletes. Practical Applications: Coaches and players should understand the significant gap between average performance in top division college soccer and even third-tier US professional soccer. This understanding may help drive coaches to design better programs, and players to work harder, to better match the demands of the next level of competition. Strength and conditioning coaches and training staffs who work with collegiate soccer players should increase their focus on improving change of direction agility and maximum speed development, as these were seen to be the largest gap between professional and college players.